Effects of nutrient addition and clipping on biomass production of invasive and native annual Asteraceae plants. (28th May 2018) - Huang, Q Q; Fan, Z W; Li, X X; Wang, Y; Liu, Y; Shen, Y D
Summary: Invasive plants dominate many habitats and cause significant harm to native plants, agriculture and the wider environment. Clipping by mowing machines has been a common method to control invasive plants, but whether it can reduce the performance of invaders and increase the performance of co‐occurring natives is not known. This study examined the effects of soil nutrient conditions and clipping on the performance of three invasive and three co‐occurring native annual Asteraceae plants under either isolated or competitive conditions. Clipping tended to reduce the aboveground biomass of the invasive plants more than that of the native plants under low, but not under high nutrient conditions. However, invasive plants still produced an aboveground biomass equal to, or larger than, that of native plants under the low nutrient and clipping treatment combination. Nutrient addition increased the aboveground biomass of the invasive plants more than that of the native plants, although this was only marginally significant under competitive conditions. Clipping did not reduce the performance advantage of invaders over natives under high soil nutrient conditions. The ability of invaders to benefit more from nutrient addition, along with its ability to perform equally well, or better than, the native plants after human mechanical control (i.e. clipping), may explain their high abundance and dominance in many habitats.